Journey to Goliad - Cuate, Melodie A.; Starr, Lindsay (Lubbock, Tex. : Texas Tech University Press, 2009)
When Mr. Barrington takes his students to an archaeological dig at Presidio La Bahia, Hannah, Jackie, and Nick travel back to 1836, just weeks before the Texan and Mexican armies clash at the Battle of Coleto.
Keywords: Alavez, Francisca -- Fiction; Goliad (Tex.), Goliad Massacre, 1836 -- Fiction; Time travel -- Fiction; Texas -- Fiction -- History -- 19th century; School stories